Nursing students' reflections on the learning experience of a unique mental health clinical placement. (November 2016) - Patterson, Christopher; Moxham, Lorna; Brighton, Renee; Taylor, Ellie; Sumskis, Susan; Perlman, Dana; Heffernan, Tim; Hadfield, Louise
Abstract: Introduction: There exists a need for innovative thinking to identify new clinical placement opportunities for nursing students. Recovery-based clinical placements for mental health nurse students remain unique and require investigation. Aim: To examine the learning experience of Bachelor of Nursing students who undertook an innovative mental health clinical placement known as Recovery Camp . Design: This study incorporated qualitative analysis of written reflections. Using Braun and Clarke's (2006) six phases of thematic analysis the corpus of student reflections were reviewed by three members of the research team independent to each other. Findings: Four themes emerged. The theme of Pre-placement Expectations incorporates participant foci on pre-conceptions of Recovery Camp . The theme of Student Learning incorporates the ways in which participants recognised the experience of Recovery Camp influenced learning. Reflections themed under the title Placement Setting include discussion of the Recovery Camp as a clinical placement. The theme of Future Practice incorporates students' reflections on how they plan to practice as nurses as a result the learning experiences of Recovery Camp . Conclusions: An immersive clinical placement such as Recovery Camp can influence students' perceptions of people with mental illness, have a positive impact on student learning and influence students' decisions about future practice. The learning experience of nursing students whom attend unique, recovery-orientated clinical placements can be both positive and educative. Highlights: Recovery Camp was developed to enhance students understanding about the lived experience of a person with mental illness Student critical reflections can be utilised as a means of examining the efficacy and value of clinical placements. Findings demonstrate how a collaborative learning environment may develop future nurses' in-depth knowledge of recovery.